2002
DOI: 10.1128/jvi.76.21.10776-10784.2002
|View full text |Cite
|
Sign up to set email alerts
|

The Major Phosphorylation Sites of the Respiratory Syncytial Virus Phosphoprotein Are Dispensable for Virus Replication In Vitro

Abstract: The phosphoprotein (P protein) of respiratory syncytial virus (RSV) is a key component of the viral RNA-dependent RNA polymerase complex. The protein is constitutively phosphorylated at the two clusters of serine residues (116, 117, and 119 [116/117/119] and 232 and 237 [232/237]). To examine the role of phosphorylation of the RSV P protein in virus replication, these five serine residues were altered to eliminate their phosphorylation potential, and the mutant proteins were analyzed for their functions with a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
69
1
3

Year Published

2006
2006
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(73 citation statements)
references
References 33 publications
0
69
1
3
Order By: Relevance
“…Previous studies have indicated that the P's of respiratory syncytial virus (RSV) (25) and Sendai virus (SeV) (26) play roles in the transcription and replication of these viruses. A recent study also showed that a phosphorylation site within the P of parainfluenza virus 5 plays a positive role in viral mRNA synthesis and virus growth (27).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have indicated that the P's of respiratory syncytial virus (RSV) (25) and Sendai virus (SeV) (26) play roles in the transcription and replication of these viruses. A recent study also showed that a phosphorylation site within the P of parainfluenza virus 5 plays a positive role in viral mRNA synthesis and virus growth (27).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, P protein phosphorylation may have a role in the distinction between vRdRpR and vRdRpT (Collins et al, 2001 Phosphorylation at S237 in vitro has been suggested (Mazumder et al, 1994). Phosphorylation at these residues is not required for viral transcription or replication, either to support M2-1 transcriptional activities or for the viral growth cycle (Asenjo et al, 2005;Lu et al, 2002;Villanueva et al, 2000).…”
mentioning
confidence: 99%
“…Thus, P protein phosphorylation may have a role in the distinction between vRdRpR and vRdRpT (Collins et al, 2001 Phosphorylation at S237 in vitro has been suggested (Mazumder et al, 1994). Phosphorylation at these residues is not required for viral transcription or replication, either to support M2-1 transcriptional activities or for the viral growth cycle (Asenjo et al, 2005;Lu et al, 2002;Villanueva et al, 2000).Nevertheless, in a P protein variant with all of these residues replaced by non-phosphorylatable residues (VPm30) (Fig. 1a), phosphorylation was detected at S and T residues when it was expressed transiently in HEp-2 cells and labelled with [ 32 P]orthophosphate in the presence of 1 mM okadaic acid (OKA) to inhibit cellular phosphatases PP2A and PP1 completely (Bialojan & Takai, 1988) (Fig.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…22 Furthermore, although PP5 is present in both nuclear and cytoplasmic compartments, its subcellular localization predominates in the nucleus, 19,23 a site where dephosphorylation of FKBP52 is most likely to occur. And finally, as PP5 contains a C-terminal catalytic domain structurally related to the PP1/PP2A/PP2B family and an N-terminal regulatory domain consisting of three tetratricopeptide repeats (TPRs) that usually mediate protein-protein interaction, 24 it has been demonstrated that PP5 interacts with multiple unrelated target proteins through the TPR domain, [25][26][27][28][29][30][31] and FKBP52 is known to contain a TPR domain. 32,33 In the current study, we used various known inhibitors of protein Ser/Thr phosphatases to pretreat an established human embryonic kidney cell line 293, in which FKBP52 is present predominantly in the Ser/Thr phosphorylated form.…”
mentioning
confidence: 99%